2019
DOI: 10.1142/s0218196719500243
|View full text |Cite
|
Sign up to set email alerts
|

Morita equivalence of factorizable semigroups

Abstract: A semigroup is called factorizable if each of its elements can be written as a product. We study equivalences and adjunctions between various categories of acts over a fixed factorizable semigroup. We prove that two factorizable semigroups are Morita equivalent if and only if they are strongly Morita equivalent. We also show that Morita equivalence of finite factorizable semigroups is algorithmically decidable in finite time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…[11]). However, in the subclass of factorizable semigroups, it is sufficient to consider strong Morita equivalence, which coincides with the category theoretical Morita equivalence by Theorem 4.11 in [10].…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…[11]). However, in the subclass of factorizable semigroups, it is sufficient to consider strong Morita equivalence, which coincides with the category theoretical Morita equivalence by Theorem 4.11 in [10].…”
Section: Introductionmentioning
confidence: 92%
“…By Laan and Reimaa [10], we have that a semigroup S is factorizable if and only if S ⊗ S is a firm semigroup. In the same article it is shown that A ⊗ S B = A ⊗ S⊗S B holds for factorizable semigroups S. While we do not know, whether Theorem 2.12 holds for factorizable semigroups, we can conclude the following.…”
Section: If T Is a Semigroup With Common Weak Local Units Then All St...mentioning
confidence: 99%
See 2 more Smart Citations
“…By Proposition 4.9 in [16], these functors are inverse equivalence functors. We also recall that is considered as a semigroup with the multiplication , and the action of is .…”
Section: Morita Invariancementioning
confidence: 99%